Intersectionality in the Maze of Oppression: A Feminist Criminology Analysis of Systematic Vulnerability and Exploitation of Indonesian Women Trafficked to Cambodia - Anugrah, Reza; Mutaharina, Lifiana Alanisya (UI Scholars Hub, 2025)
This study explores the vulnerability of Indonesian women to the crime of human trafficking in Cambodia, analyzing its structural and patriarchal roots. Employing a qualitative methodology through literature review, the paper delineates how socio-economic disparities and limited employment opportunities in Indonesia drive women toward illegal job offers that ultimately result in exploitation. Human trafficking syndicates exploit traditional gender constructs and manipulate identities to entrap victims, even involving women as alleged perpetrators. Criminological and legal analyses reveal a shift toward more complex forms of transnational crime, exacerbated by the use of digital technology. Although the Law of the Republic of Indonesia Number 21 of 2007 on the Eradication of the Crime of Human Trafficking (hereinafter referred to as the “Human Trafficking Law”) exists, its implementation is hindered by gender-biased law enforcement and a lack of responsiveness, resulting in the double victimization of survivors. Over 60% of trafficking victims are women, yet many of them face criminalization. The concept of human security becomes an illusion as the state fails to provide adequate protection and empowerment. Comprehensive legal reform, a victim-centered approach, and strengthened cross-border cooperation are urgently required to address this issue.